2013
DOI: 10.1371/journal.pone.0080095
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Selection? A Multi-Dimensional Profile of People Dispensed Opioid Analgesics for Persistent Non-Cancer Pain

Abstract: ObjectivesThis study investigates utilisation patterns for prescription opioid analgesics in the Australian community and how these are associated with a framework of individual-level factors related to healthcare use.MethodsSelf-reported demographic and health information from participants in the 45 and Up Study cohort were linked to pharmaceutical claims from 2006–2009. Participants comprised 19,816 people with ≥1 opioid analgesic dispensing in the 12-months after recruitment to the cohort and 79,882 people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 23 publications
6
40
0
1
Order By: Relevance
“…Extant literature documents that opioid users report severe pain [64], and have higher healthcare utilization compared with non-opioid users [38,65,66]. Our findings suggest that similarly to other chronic pain conditions, MFS individuals who use opioids report more intense, frequent, and non-remitting pain.…”
Section: Physical and Psychological Burden In Opioid Usersmentioning
confidence: 54%
“…Extant literature documents that opioid users report severe pain [64], and have higher healthcare utilization compared with non-opioid users [38,65,66]. Our findings suggest that similarly to other chronic pain conditions, MFS individuals who use opioids report more intense, frequent, and non-remitting pain.…”
Section: Physical and Psychological Burden In Opioid Usersmentioning
confidence: 54%
“…The complexity of the chronic pain patient, in terms of multiple social, mental health and physical wellbeing issues (14,40), makes treatment complicated. With the addition of BPD, which has often been associated with a 'difficult patient' (9) treatment can become more…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to identify factors associated with depression developing after the commencement of opioid medications that might differ from those associated with the onset of pain itself. Where previous research has been limited by measuring opioid use through prescriptions or specific populations (Rogers et al, 2013;Scherrer et al, 2014), the current study is unique in using a community sample self-reporting consumption of opioids, including those purchased over the counter, and additionally controlling for pain-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study found individuals who were receiving opioid treatment were more likely to report high levels of psychological distress compared with individuals not receiving opioid medications (Rogers et al, 2013). Additionally, opioid-naïve patients with chronic pain without a recent history of depression have been found to be at greater risk of developing depression the longer they were taking opioid medications (Scherrer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%